1975
DOI: 10.1111/j.1749-6632.1975.tb29159.x
|View full text |Cite
|
Sign up to set email alerts
|

THE SPECIFICITY OF FETAL IgM: ANTIBODY OR ANTI‐ANTIBODY?

Abstract: Reference materials were produced to standardize the immunoglobulin class specificity and potency of immunofluorescent anti-IgM conjugates used for diagnostic tests for congenital syphilis. In attempting to mimic essential immunologic characteristics of syphilitic and nonsyphilitic infant sera, we evaluated these sera in comparison with processed adult sera. We were quite surprised to discover that some syphilitic babies do not produce significant quantities to IgM antibody to T. pallidum in response to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

1979
1979
2010
2010

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(37 citation statements)
references
References 33 publications
1
35
0
1
Order By: Relevance
“…1977;Kangro et al 1978). It may also occur in infants: Urquhart, Logan & Izatt (1971) detected it by agglutination of sensitized group 0 Rh positive red cells in cases of sudden unexplained death in infancy, and Reimer et al (1975) demonstrated it by means of the fluorescent treponemal antibody test in two babies with suspected congenital syphilis. Reimer and his colleagues suggested that IgM of this type might be formed as an immune response to complexes of maternal IgG with the infecting agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1977;Kangro et al 1978). It may also occur in infants: Urquhart, Logan & Izatt (1971) detected it by agglutination of sensitized group 0 Rh positive red cells in cases of sudden unexplained death in infancy, and Reimer et al (1975) demonstrated it by means of the fluorescent treponemal antibody test in two babies with suspected congenital syphilis. Reimer and his colleagues suggested that IgM of this type might be formed as an immune response to complexes of maternal IgG with the infecting agent.…”
Section: Discussionmentioning
confidence: 99%
“…A solid-phase technique, with antigen adsorbed onto polystyrene balls, was used by Kalimo et al (1976) to detect IgG antibody, and by Meurman, Viljanen & Granfors (1977) to detect IgM in patients with acute infection. Kangro, Pattison & Heath (1978) Reimer et al (1975) that IgM from an infant congenitally infected with one pathogen might become attached to preparations of another, provided that maternal IgG specific for the latter were present, we have also examined sera from infants with congenital toxoplasmosis and cytomegalovirus (CMV) infection.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, a determinação de IgM em DCC está sujeita a muitas causas de erro, tanto biológicas como metodológicas. Entre as primeiras, que dão origem freqüentemente a resultados falso-positivos, encontram-se, entre outras, a passagem anormal de IgM materna ao feto, o chamado "derrame placentário" (Mc Craken et al, 1969) e a presença de anticorpos tipo Fator Reumatóide, que reagem com a IgG materna quando existem diferentes alótipos na mãe e no feto (Reimer et al, 1975).…”
Section: Métodos Parasitológicos A) Diretosunclassified
“…However, in clinical studies of this antibody, falsely negative results were obtained in 20-39% of cases, and false posi tives, due to IgM-rheumatoid factor (IgM-RF), in up to 10% [20]. Definitive prospec tive clinical investigations using rigorous case definitions and standardized methodol ogy have not been done, and the place of this test in the clinical practice of pediatrics re mains questionable [21], Assessment of total fetal IgM levels repre sents the third strategy which has been used in the diagnosis of cogenital syphilis [21 -24], Use of this nonspecific criterion has been equivocal, as a multitude of congenital ab normalities [25][26][27][28][29] may cause elevations in total fetal serum IgM levels.…”
Section: Serodiagnosis: a Trend Towards Fetal/ Neonatal Igm-specific mentioning
confidence: 99%
“…Early com plement production in the fetus begins in the first trimester; however, the alternate path way with its opsonic, chemotactic and cyto lytic activities may be delayed [62], The con genitally infected fetus is in the immunologically distinct position of dealing with an invading organism not only with his own developing immune defense mechanisms but also with passively acquired 'foreign' IgG. The maternal IgG in turns appears to induce IgM-RF which are detectable not only in this disease, but in a number of other congenital infections [63,64], There appears to be no association be tween congenital syphilis and first-trimester fetal loss (stillbirths) or congenital anoma lies; foci of necrosis are not apparent, nor are inflammatory changes and treponemes so rare that silver staining alone is insufficient to assure demonstration [60], Second-tri mester fetal losses tend to occur late in the trimester and are associated with few organ isms and minimal morphologic changes. Judge et al [65] have found that morpho logic changes are directly proportional to the numberof organisms and the maturity of the fetal immune system; severe disease associ ated with large numbers of organisms.…”
Section: Pathogenesis: a Need To Understand The Ontogeny And Impact Omentioning
confidence: 99%